Two-year neurological outcome of very-low-birth-weight children with prenatal absent or reversed end-diastolic flow velocity in the umbilical artery - Chen-Yu Chen; Kuo-Gon Wang; Shwu-Meei Wang; Chie-Pein Chen (Elsevier, 2013)
Objective: The aim of this study was to investigate the 2-year neurological outcome of very-low-birth-weight (VLBW) children who had abnormal umbilical blood flow velocity prenatally. Materials and Methods: We performed a prospective collection of infants prenatally diagnosed with abnormal umbilical blood flow velocity at a tertiary referral center from January 1, 2001 to September 30, 2005. VLBW children with prenatal absent or reversed end-diastolic flow velocity (AREDV) in the umbilical artery were investigated and compared with two similar demographic control groups of VLBW children without AREDV: one group with fetal growth restriction and the other without it. A follow-up study at 2 years of age for Mental Developmental Index (MDI) and Psychomotor Developmental Index (PDI) of the Bayley Scales among the three groups was analyzed. Results: Twenty-four VLBW children were identified to have AREDV prenatally, of whom four died during the neonatal period. After 2 years, five children were lost to follow-up and 15 were rescued, of whom 11 had absent end-diastolic velocity and four reversed end-diastolic velocity. We compared the remaining 15 children with the two control groups [28 children in the matched control group with intrauterine fetal growth restriction (IUGR), and 38 children in the matched control group without IUGR], and no significant differences were found in MDI (p = 0.938) and PDI (p = 0.496) scores at 2 years of age. However, we also surveyed the children with a gestational age of ≤29 weeks and found a significant difference in MDI scores (p = 0.048), but not in PDI scores (p = 0.219), among the three groups. Conclusion: VLBW children delivered earlier than 29 gestational weeks with abnormal umbilical blood flow velocity prenatally have greater mental developmental delay at 2 years of age.